Effect of Sechium edule on chemical induced kidney damage in experimental animals (Bangladesh Journal of Pharmacology, 2012)
The aqueous extract of leaves of Sechium edule was evaluated for its protective activity against gentamicin, potassium dichromate-induced nephrotoxicity and streptozotocin-induced diabetic nephropathy in experimental animals. In these three conditions, the extract of S. edule (200 mg/kg) has significantly (p